Psychology a journey - Coon, Dennis; Mitterer, John O. (Wadsworth/Cengage Learning, 2013)
Each chapter of this book takes you into a different realm of psychology, such as personality, abnormal behaviour, memory, consciousness, and human development. Each realm is complex and fascinating, with many pathways, landmarks, and detours to discover.